FEATURES AND PROSPECTS FOR THE DEVELOPMENT OF THE E-COMMERCE BUSINESS MODEL - Kalandarov Ravshan Abdukayumovich; Radjabova Malikaxon Obidjon kizi (Western European Studies, 2024)
This article provides proposals and recommendations on the large-scale use of the modern concept of e-business, providing high economic efficiency for the formation and further consistent development of the economy of Uzbekistan, application of modern information technologies, mathematical models and methods, theoretical and methodological e-business, finding an effective solution to a number of economic issues in our country.
Keywords: E-commerce; e-commerce business model; e-business; e-commerce market